K-State Research and Extension An Informal Report to the Kansas Legislature - Johnson, Marc A. (My University, 2003)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2003, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
Keywords: Administrative and Research Reports; legislature